(untitled) (Research, Society and Development, 2021)
Introduction: It is speculated that a modality as intense as the High Intensity Interval Training (HIIT) could be one of the factors to generate greater number of injuries in runners. Objective: To review, in the literature, studies that record injuries caused by HIIT in recreational or running professionals. Methodology: This is a literature review using the Latin American and Caribbean Literature in Health Sciences databases, National Library of Medicine and The National Institute of Health, US National Library of Medicine, Scientific Electronic Library Online with the descriptors "high intensity interval training", "injury", "running" and "runners" with their variations. The search was limited based on the availability of text (full text available), date of publication (from January 2000 to March 2020), species (humans), without language restriction. Inclusion of any type of runners (recreational and professional) was allowed. Articles that did not use HIIT or that had no relationship between training and injuries were excluded from the research. Results: 32 articles were chosen to read the summary and those that did not match the purpose of this study were excluded. Seven articles were selected that met the proposed criteria and the following steps were followed in that order: exploratory reading; analysis of the texts, ending with the performance of interpretative reading and writing. Conclusion: There are still few studies that investigated the occurrence of injuries with the practice of HIIT in runners. The samples were small and presented different samples of the different running practices as elite and recreational runners.